The Inhibitory Effect of Regulatory T Cells on the Intimal Hyperplasia of Tissue-Engineered Blood Vessels in Diabetic Pigs - Guo, Fengjie; Ren, Zhipeng; Liu, Dongxu; Wang, Linghui; Hou, Xiaobin; Chen, Wen (Frontiers in Bioengineering and Biotechnology, 2022)
Severe inflammatory response and functional impairment of endothelial progenitor cells (EPCs) often lead to the implantation failure of EPC-captured tissue engineered blood vessels (TEBVs) in diabetes. Regulatory T cells (Treg cells) are the most important inhibitory immune cells, but their effects in angiogenesis remains undefined, and the differences in microenvironment may be an important reason. Here we constructed TEBV coated with an anti-CD34 antibody functionalized heparin-collagen multilayer (anti-CD34 antibody modified TEBV) using layer by layer self-assembly. Then TEBVs were implanted into diabetic pigs. All TEBVs remained unobstructed 60 days after implantation, although varying degrees of intimal hyperplasia were detectable. Severe intimal hyperplasia was observed in the control group and peripheral injection of Treg cells group. Intravenous injection of Treg cells significantly inhibited intimal hyperplasia, inflammation and cell apoptosis. Moreover, intravenous injection increased the proportion of circulating EPCs, while peripheral injection did not have these effects and reduced microvessel density around the TEBV. Interestingly, many Nestin+ cells could be detected in TEBVs, most of which were fusiform, showing the characteristics of smooth muscle cells. Treg cells intravenous transplantation markedly reduced the number of Nestin+ cells in the TEBV. In conclusion, Treg cells inhibited the intimal hyperplasia of TEBVs in diabetic pigs by promoting EPCs mobilization, anti-inflammatory action and cellular protection.